Structural, Spectral and Thermal Studies of Novel Tridentate Schiff Base Ligand Type (NOO) as Donor Atoms Derived from Nalidixic Acid and 4-Aminoantipyrine and Metal Complexes and Evaluation of their Biological Activity - Hawraa K. Salloom (Journal of Global Pharma Technology, 2020)
In this study, a novel Schiff base (E)-4-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)-1-ethyl-7-methyl-1,4-dihydro-1,8-naphthyridine-3-carboxylic acid [HL] was synthesized from nalidixic acid 4-Aminoantipyrine and its metal complexes for metal ions M=VO, Mn, Co, Ni, Cu, Zn, Pd and Pt in ethanol and acetic acid with mole ratio (M:L) (1:2). All complexes have general composition [VO (L)(SO4)] H2O, [Mn(L)2], [Co(L)2] H2O, [Ni(L)2] H2O, [Cu(L)2] H2O, [Zn(L)2].H2O, [Pd(KL)2] and [Pt(KL)Cl2] Cl2 where L- =C23H22N5O3. The ligand and all complexes were characterized by modern spectroscopic (FT-IR, UV Vis, 1HNMR, Mass spectroscopy, atomic absorption), along with elemental microanalysis, magnetic susceptibility measurements, thermal analyses, chloride content and molar conductance. In addition to evaluated their biological activity against one type of bacterial and one type fungus. Based on date for all techniques we suggested that all the prepared complexes have octahedral geometry accept [[VO (L)(SO4)] H2O] square pyramidel geometry and [Pd (KL) 2] Square planer geometry. The value of antibacterial activity of this prepared complexes showed higher inhibition activity compared to the free ligand and starting material.Keywords: Nalidixic Acid, 4-Aminoantipyrine, Metal complexes, Biological activity.Introduction